Desmoglein-3 overexpression in oral squamous cell carcinoma is associated with metastasis formation and early recurrence: An immunohistochemical study. Issue 3 (March 2022) - Troeltzsch, Matthias; Künzel, Verena; Haidari, Selgai; Troeltzsch, Markus; Otto, Sven; Ehrenfeld, Michael; Probst, Florian; Knösel, Thomas
Abstract: The purpose of this study was to determine the expression patterns of specific desmosomal cadherins (desmogleins [DSG] 1/2/3) in oral squamous cell carcinoma (OSCC), and to examine possible associations with clinicopathological parameters and recurrence rates. Changes in desmosomal cadherin assembly may promote tumor metastasis formation. Patients with surgically treated OSCC with 36–60 months of follow-up (median 46 months) qualified for inclusion in this retrospective cohort study. Demographic, clinical and pathohistological data were collected. DSG-1/2/3 expression patterns were determined by an immunohistochemical approach on tissue microarrays. Descriptive and inferential statistics and survival analyses were computed (p ≤ 0.05). The study sample consisted of 88 patients (female: 38; male: 50; average age: 63.02 ± 17.5 years). DSG-3 overexpression was detected in 45 of 88 specimens. The expression rates for DSG-1 (28/88) and DSG-2 (14/88) were low and inconspicuous. DSG-3 overexpression was significantly associated with poor histologic differentiation (G3, p = 0.001), the presence of cervical node metastasis at primary diagnosis (N+ status, p = 0.001) and early recurrence (p = 0.001). Due to its possible relevance for lymph node metastasis formation and early OSCC recurrence, determination of DSG-3 expression in OSCC specimens may be a valuable tool for treatment planning and post-therapeutic risk assessment. Highlights: Desmoglein-3 (DSG-3) is overexpressed in a significant number of oral squamous cell carcinomas (OSCC). The expression status of other desmogleins (DSG-1 and -2) in OSCC does not differ from normal oral tissues. DSG-3 overexpression in OSCC correlates with the occurrence of lymph node metastases and an increased likelihood for recurrence. Poor histologic grade (G-status) of OSCC and DSG-3 overexpression are associated.